Pendampingan Bimbingan Belajar Siswa MI di Desa Sumber Sari - Sri Enggar Kencana Dewi; Eli Rotama; Ratih Purnama Pertiwi; Nesi Anti Andini; Nor Kholidin; Resti Septikasari; Tri Ratna Dewi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STKIP Nurul Huda, 2022)
The current condition is that the community wants each of their children to pursue formal school education to graduate with maximum grades so they can continue on to a higher school level. Various kinds of efforts are made for their children to be able to understand the learning that takes them at school. If you want to increase students' understanding of their learning, many of them enroll their children in non-formal education, namely tutoring institutions. The method used directly provides assistance to students at the SD / MI level. The implementation of this tutoring includes motivating students, which is done by providing games or ice breaking before or after tutoring, providing an explanation of the subject matter if there are students who do not understand at school and the third is by providing homework services provided by the school. , so that students can better understand in doing homework given by the father or mother of the teacher thus students will be greatly assisted if they experience difficulties in their learning.